The risk control of rollover safety for new energy vehicles based on wire controlled chassis system - Wang, Guosheng (Frontiers in Mechanical Engineering, 2025)
IntroductionTechnological innovation is the key to ensuring the safety performance of new energy vehicles, which is crucial for ensuring the safety performance of new energy vehicles.MethodsIn order to ensure the safety and dynamism of new energy vehicles, a fuzzy dynamic Markov control strategy was adopted to design a vehicle’s anti-rollover wire controlled chassis system, analyze its fuzzy failure efficiency, and combine fault tree analysis to assess the safety integrity level of the vehicle.ResultsThe results showed that the proposed control strategy achieved a wheel turning angle error of within 0.002° for new energy vehicles, indicating good vehicle performance. In the case of sharp turns, the proposed control strategy had a body roll angle of basically within 3.0°. The designed new energy vehicle reached the automotive safety integrity level D, which means that the designed system can maintain functional safety in the event of potential faults, significantly reducing the risk of vehicle accidents and ensuring passenger safety and vehicle dynamic stability.DiscussionBy reducing the risk of vehicle rollover under extreme driving conditions, vehicle handling and reliability could be improved, ensuring that new energy vehicles can operate more safely in a wider range of real-world scenarios. This provides a certain technical theory for the safety control of car rollover, which is helpful for the safety risk management of vehicles.